The remains of the day - Ishiguro, Kazuo, 1954- (Vintage Books, a division of Random House, 1993)
"This is Kazuo Ishiguro's profoundly compelling portrait of a butler named Stevens. Stevens, at the end of three decades of service at Darlington Hall, spending a day on a country drive, embarks as well on a journey through the past in an effort to reassure himself that he has served humanity by serving the "great gentleman," Lord Darlington. But lurking in his memory are doubts about the true nature of Lord Darlington's "greatness," and much graver doubts about the nature of his own life." --Provided by publisher.